Mapping of antigenic determinant regions of the Bor56 protein of Orientia tsutsugamushi. - Seong, S Y (1997)
The 56-kDa protein (Bor56) of Orientia tsutsugamushi is an immunoprotective antigen and is the target molecule of neutralizing antibodies. This antigen is recognized by almost all of the serum antibodies produced by patients in the convalescence phase of scrub typhus. We expressed the Bor56 open reading frame in Escherichia coli and generated from it a series of deletion constructs as MalE fusion proteins. Antibody-binding domains were characterized by using patient sera, mouse monoclonal antibodies (MAbs), and Bor56-immunized-mouse sera. None of the antibodies bound to a fusion protein containing the carboxy-terminal 140 amino acids (aa) of the Bor56 protein, suggesting that the carboxy-terminal domain of Bor56 is not exposed on the surface of the molecule. Human immunoglobulin M (IgM) antibodies predominantly bound to antigenic domain I (AD I; amino acids [aa] 19 to 113) and AD III (aa 243 to 328). Human IgG antibodies also showed preferential binding to AD I. The epitope recognized by strain-specific MAb (KI4) or group-specific MAb (KI57) was mapped to AD II (aa 142 to 203). Mouse serum antibodies, elicited by immunization with deletion mutants, consistently bound to AD III. Moreover, the carboxy-terminal 140 aa of the Bor56 protein did not elicit an antibody response in C3H/HeDub mice. A model of the antigenic structure of Bor56 is presented and discussed. These results suggest that antigenic fragments from AD I and AD III are useful in the induction of humoral immunity against O. tsutsugamushi. These antigenic analyses provide an important foundation for further analyses of the neutralizing-antibody responses generated during rickettsial infections. They also provide potential peptide substrates for diagnostic assays and vaccine strategies.